A Systematic Literature Review on the Relationship between Sharia Regulatory Framework and Islamic Fatwa - Salisu, Auwal; Saniff, Shereeza Mohamed (Sharia Business Management UIN Raden Intan Lampung, 2023)
Sharia Regulatory Framework (SRFW) ensures all activities and business transactions by IFIs that are free from non-allowable elements such as Riba (Usury), Gharar (Risks) etc. When such transactions have met the stringent requirements and have fulfilled the Sharia compliance mechanism, only then the transactions by the Islamic Financial Institutions (IFIs) are lawful. However, Islamic Fatwa (IF) is not embedded into the current Sharia compliance mechanism. There is needs to be a study to establish the relationship between SRFW and Islamic Fatwa. Yet, there are still not enough studies that conduct a systematic review on this. This study has two objectives. Firstly, to identify the relationship between SRFW and IF. Secondly, to show how Sharia compliance mechanism can be completely established after effective use of IF. The articles were chosen using one leading database, SCOPUS, and one supporting database, Google Scholar, and manual searching. Several important contributions were made by the study to regulators and policymakers. Finally, the findings demonstrate that IFIs could be better regulated in accordance with Sharia principles with effective use of IF through SRFW, the study recommend the specific research areas and content that should focus on future studies.